Expanding the Spectrum of Pediatric NTRK-rearranged Mesenchymal Tumors. (April 2019) - Davis, Jessica L.; Lockwood, Christina M.; Stohr, Bradley; Boecking, Carolin; Al-Ibraheemi, Alyaa; DuBois, Steven G.; Vargas, Sara O.; Black, Jennifer O.; Cox, Michael C.; Luquette, Mark; Turpin, Brian; Szabo, Sara; et al.
Abstract : Pediatric mesenchymal tumors harboring variant NTRK fusions ( ETV6 -negative) are being increasingly described; however, the histologic and clinical features of these variant NTRK tumors and their relationship to classic infantile fibrosarcoma are not well characterized. A better understanding of the clinicopathologic features of these tumors is necessary, and would aid in both early diagnosis and treatment. Therefore, the aim of this study was to characterize a series of pediatric NTRK -rearranged mesenchymal tumors, including classic ETV6-NTRK3 fused tumors and tumors with variant (non- ETV6 ) NTRK fusions. The clinical features, morphology, immunophenotype, and genetics of 12 classic ETV6-NTRK3 fused infantile fibrosarcoma and 18 variant NTRK- rearranged mesenchymal tumors were evaluated. For both classic and variant groups, the age at diagnosis ranged from birth to 15 years (median, 4 mo) with no sex predilection; the most common sites involved were the extremities and trunk. The rate of local recurrence and metastasis were not significantly different (recurrence rate: 11% classic, 40% variant; metastatic rate: 18% classic, 25% variant). Classic and variant NTRK tumors had an overlapping spectrum of histologic features, containing haphazardly arranged primitive cells in a myxoid background and/or spindle cells in long fascicles. Both groups showed diffuse pan-TRK expression by immunohistochemistry. Otherwise, the immunoprofile was nonspecific, but similar between both groups. No statistical difference was seen in any clinicopathologic feature between the classic ETV6-NTRK3 and variant fusion cohorts. Pediatric NTRK -rearranged mesenchymal tumors with both classic and variant fusions likely represent a spectrum of disease with shared, recognizable cliniopathologic features. Abstract : Supplemental Digital Content is available in the text.